Correlation of plasma C-reactive protein levels to sialic acid and lipid concentrations in the normal population - Qvist, R.; Ismail, I.S.; Muniandy, S.; Vellasamy, K.M.; Chinna, K. (2007)
Aim of this study was to investigate the relationship between sialic acid component and C-reactive protein and lipids in the plasma of 80 healthy subjects. Levels of sialic acid, C-Reactive Protein (CRP) and plasma lipids were measured in a normal population consisting of 80 subjects. The possible correlation between sialic acid and CRP was also studied. The total sialic acid concentration was 2.61±0.61 mM L-1, CRP (2.52±2.32 mmole L-1), total cholesterol (5.504±1.28 mM L-1), triglycerides (1.31±0.87 mM L-1), low density lipoprotein (3.51±1.11 mM L-1) and high density lipoprotein (1.40±0.37 mM L-1). There was a positive correlation between sialic acid and CRP (r = 0.283, p<0.05). However, there was no correlation between CRP and the plasma lipids.